2021
DOI: 10.7150/ijbs.52319
|View full text |Cite
|
Sign up to set email alerts
|

ITGB1 enhances the Radioresistance of human Non-small Cell Lung Cancer Cells by modulating the DNA damage response and YAP1-induced Epithelial-mesenchymal Transition

Abstract: Objectives: Radiotherapy has played a limited role in the treatment of non-small cell lung cancer (NSCLC) due to the risk of tumour radioresistance. We previously established the radioresistant non-small cell lung cancer (NSCLC) cell line H460R. In this study, we identified differentially expressed genes between these radioresistant H460R cells and their radiosensitive parent line. We further evaluated the role of a differentially expressed gene, ITGB1, in NSCLC cell radioresistance and as a potential target f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 68 publications
3
41
0
Order By: Relevance
“…[28] During EMT, not only the interactions of cell-cell and cell-extracellular matrix are remodeled, but also the cancer stem cell properties, enhanced DNA damage response and antioxidant activity abilities are obtained. [29,30] In this study, we found that irradiation induction promoted ZIP7 and ZEB1 expression, and the occurrence of EMT. Knockdown of ZIP7 could downregulate ZEB1 expression, but upregulate Ecadherin expression, and both of which could be partially reversed by Py treatment.…”
Section: Discussionsupporting
confidence: 52%
“…[28] During EMT, not only the interactions of cell-cell and cell-extracellular matrix are remodeled, but also the cancer stem cell properties, enhanced DNA damage response and antioxidant activity abilities are obtained. [29,30] In this study, we found that irradiation induction promoted ZIP7 and ZEB1 expression, and the occurrence of EMT. Knockdown of ZIP7 could downregulate ZEB1 expression, but upregulate Ecadherin expression, and both of which could be partially reversed by Py treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Integrins provide yet another link between ECM structure and DNA damage-induced apoptosis ( Hoyt et al, 1996 ; Sethi et al, 1999 ; Hodkinson et al, 2006 ; Jinushi et al, 2012 ; Ahmed et al, 2018 ; Kowalski-Chauvel et al, 2018 ; Hou et al, 2019 ; Jung et al, 2019 ; Naci et al, 2019 ; Li et al, 2021 ). Nevertheless, the connection between adhesion and apoptosis is not linear and integrin binding to the ECM can either promote or prevent cells, in particular cancer cells, from undergoing apoptosis.…”
Section: The Impact Of Dna Damage On Ecm Remodelingmentioning
confidence: 99%
“…We found six key proteins of focal adhesion pathway, SHC1, ACTB, ACTN1, COL1A1, FLNA, ITGB1, and MYL12B, in the results of mass spectrometry. Previous studies have shown that the activation of ITGB1/FAK pathway signal can promote EMT and angiogenesis in lung cancer, liver cancer and non-small cell lung cancer ( Guo et al, 2020 ; Wang and Chang, 2020 ; Li et al, 2021 ). The expression and localization of DCBLD2 on the cell membrane showed obvious polarity like ITGB1 when HCT116 cells were cultured in 3D condition, which was consistent with the phenotype of focal adhesion.…”
Section: Discussionmentioning
confidence: 99%